Pemanfaatan Origami dan Mural Pohon Semangat untuk Menguatkan Resiliensi Belajar di Sanggar Lentera Anak Bali - Helmy Syakh Alam; Eka Grana Aristyana Dewi; Muhammad Heisyan Aleandro; I Made Yuda Kusuma; I Putu Angga Pratama Putra; Putu Rahadi Sukamembah; Ignasius Elsington Jemalu (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Marginalized children are prone to developing a fixed mindset that hinders their learning persistence. This community service program aimed to strengthen the learning resilience of children at Sanggar Lentera Anak Bali through swan origami activities and a Pohon Semangat (Spirit Tree) mural. Using a descriptive participatory design, 20 participants aged 7–17 engaged in a two-hour session consisting of growth mindset psychoeducation, a structured failure simulation through origami folding, collaborative games, and commitment mural creation. Observational, interview, and documentation data were analyzed thematically. Results indicated that 90% of children shifted their verbal response from "I cannot" to "I cannot yet," as measured by the frequency of positive affirmation use following the failure simulation, alongside a notable increase in independent task persistence. The mural served as a sustained visual affirmation that supported children's self-regulation. The combination of visual-kinesthetic media, local cultural values, and a social justice orientation proved effective in building children's learning resilience, with direct relevance to SDG 4 (Quality Education) and the 5th Principle of Pancasila.